The holy madmen of Tibet - DiValerio, David M. (Oxford University Press, 2015)
"Throughout the past millennium, certain Tibetan Buddhist yogins have taken on profoundly norm-overturning modes of dress and behavior, including draping themselves in human remains, consuming filth, provoking others to violence, and even performing sacrilege. They became known far and wide as "madmen" (smyon pa, pronounced nyönpa), achieving a degree of saintliness in the process. This book offers the first comprehensive study of Tibet's "holy madmen" drawing on their biographies and writings, as well as tantric commentaries, later histories, oral traditions, and more. Much of The Holy Madmen of Tibet is dedicated to examining the lives and legacies of the three most famous "holy madmen" who were all of the Kagyü sect: the Madman of Tsang (author of The Life of Milarepa), the Madman of Ü, and Drukpa Künlé, Madman of the Drukpa Kagyü. Each born in the 1450s, they rose to prominence during a period of civil war and of great shifts in Tibet's religious culture. By focusing on literature written by and about the "holy madmen" and on the yogins' relationships with their public, this book offers in-depth looks at the narrative and social processes out of which sainthood arises, and at the role biographical literature can play in the formation of sectarian identities. By showing how understandings of the "madmen" have changed over time, this study allows for new insights into current notions of "crazy wisdom." In the end, the "holy madmen" are seen as self-aware and purposeful individuals who were anything but insane"--